INFLUENCE OF CAREER MANAGEMENT ON PERFORMANCE OF FIRMS LISTED IN THE NAIROBI SECURITIES EXCHANGE IN KENYA - KIAI, DORCAS; LEWA, PETER; KARIMI, JAMES (INDONESIAN RESEARCH SOCIETY, 2019)
The study sought to determine the influence of career management on firm performance at the firms which are listed in the Nairobi Securities Exchange. The study was anchored on resource based view theory and shareholder value maximization theory. The research design used was a cross-sectional survey, target population included the head of human resources and finance directors in all the listed firms since they were better placed and conversant with the subject of this study and were involved in the development of the policies and review of performance. Sample size comprised of 136 respondents and data was collected through structured questionnaires to meet the objectives of the study. Responses were tabulated, coded and processed by use of a computer Statistical Package for Social Science (SPSS) to analyze the data. Both descriptive and inferential statistics techniques were used to analyze the data. Findings revealed that the relationship between career management and firm performance was positive and statistically significant. The study concluded that career development and planning, career mentors/ counseling, career centres and firms planning for employee growth and progression are key career management determinants for the performance of firms listed in the Nairobi Stock Exchange (NSE) and recommended that career management practices should be widely adopted by NSE listed firms as doing so would lead to improved performance